Use of cannabinoids for the management of chronic cancer pain: Integrative review - Santos, Luiz Otávio Pereira (2022)
Objective: To present publications expressed in the world scientific literature on the use of cannabinoids in the management of chronic cancer pain. Method: Integrative literature review whose data search was performed using the descriptors “Medical Marijuana”, “Cannabinoids”, “Cannabis”, “Chronic Pain”, “Cancer Pain”, defined from the vocabulary of Health Sciences Descriptors ( DeCS), these terminologies were combined using the Boolean operator AND in the electronic databases: Medical Literature Analysis and Retrieval System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS) via the Library Virtual Health (VHL). Scientific Electronic Library Online (SciELO), Web of Science (WOS), Cinahl and Scopus via CAPES Journal Portal and Cochrane Library. Results: A total of 208 studies were identified in these databases. With 40 in Medline, 01 in LILACS, 0 in SciELO, 89 in the Scopus database, 62 in the Web of Science, 9 in the Cochrane Library and 7 in CINAHL, 27 duplicate articles were excluded, leaving 181 articles. Of these, 117 articles that did not directly address the object of this research were excluded, resulting in a final sample of 10 articles. Conclusion: There is preclinical evidence that CBD can address several of the underlying pathways of cancer, and there is preclinical and clinical evidence that CBD can be effective in treating many of the symptoms and signs associated with the disease and its orthodox treatment. , however, studies that address: administration, dosage schedules and absorption of medical cannabis in the treatment of cancer are still scarce in the literature.